Peran Guru Pendidikan Agama Kristen dalam Mengatasi Kesulitan Membaca Alkitab - Yulianingsih, Dwiati; Mangaranap Siahaan , Samuel (Shift Key : Jurnal Teologi dan Pelayanan, 2025)
This study aims to describe the role of Christian Education teachers in overcoming reading difficulties, especially when reading the Bible because students have not mastered basic reading skills. The methodology used in this study is descriptive qualitative with research data collection techniques using tests, observations, and interviews with Christian Education teachers and the principal of Melbourne Deli Serdang Private Elementary School. The results of this study indicate that Christian Education teachers play a role in overcoming reading difficulties of grade II elementary school students who take Christian Education lesson, totaling four students, namely two students are able to read slowly, one student reads simple sentences fluently and one student is still spelling, from an initial condition of not being able to read at all. With basic reading skills, the four students began to be able to read the Bible.